Introduction to probability and statistics : principles and applications for engineering and the computing sciences - Milton, J. Susan (McGraw-Hill series in probability and statistics, 2003)
Introduction to probability and counting - Some probability laws - Discrete distributions - Continuous distributions - Joint distributions - Descriptive statistics - Estimation - Interferences on the mean and variance of a distribution - Interferences on proportions - Comparing two means and two variances - Simple linear regression and correlation - Multiple linear regression models - Analysis of variance - Factorial experiments - Categorical data - Statistical quality control - Appendices.